Long-term stability of splinted anterior mandibular teeth during supportive periodontal therapy - Sonnenschein, Sarah K.; Betzler, Carlota; Rütters, Maurice; Krisam, Johannes; Saure, Daniel; Kim, Ti-Sun (Acta odontologica Scandinavica, 2017)
Objective: The aim of the study was to retrospectively assess the survival rate and stability of periodontally compromised and mobile anterior mandibular teeth after splinting in patients under supportive periodontal therapy (SPT).Materials and methods: Thirty-nine patients with splinted anterior mandibular teeth and SPT (≥1 visit/year) for 3-15 years were re-examined. Periodontal status, patient and tooth-related factors were assessed retrospectively before (baseline) and 3 years after splinting (n = 39 patients, 162 splinted teeth). For patients with splints inserted for more than 3 years, retrospective data after 5 (n = 30), 7 (n = 24), 10 (n = 16), 12 (n = 8) and 15 years (n = 4) was included, if available. At baseline, splinted teeth included at least one tooth with increased mobility combined with clinical attachment loss (CAL) ≥ 5 mm and ≥50% relative bone loss (RBL). Baseline RBL of splinted teeth was assessed for all patients. Change in RBL was assessed after 10 years, if available. Results: No splinted tooth was lost within the first 3 years after splinting. One splinted tooth was lost 7 years after baseline and one 12 years after baseline. After 3 years mean(SD) periodontal probing depth of splinted teeth decreased from 3.39(1.41) mm to 2.12(0.37) mm and mean(SD) CAL from 5.61(1.66) mm to 5.09(1.67) mm and remained stable over the observation period. No change in RBL was observed over a 10-year period (p = .213). The survival rate of the splints until fracture or debonding was 74.4% after 3 years. Conclusions: Periodontally compromised splinted teeth show a high survival-rate and periodontal stability during SPT.
Gesehen am 31.07.2018